Society without God: What the Least Religious Nations Can Tell Us About Contentment - Zuckerman, Phil (New York University Press, 2008)
Frontmatter -- Contents -- Acknowledgments -- Introduction -- 1 Society without God -- 2 Jens, Anne, and Christian -- 3 Fear of Death and the Meaning of Life -- 4 Lene, Sonny, Gitte -- 5 Being Secular -- 6 Why? -- 7 Dorthe, Laura, and Johanne -- 8 Cultural Religion -- 9 Back to the USA -- Appendix -- Notes -- Bibliography -- Index -- About the Author